Comparative phytochemical profiling, antibacterial activity, and antioxidant potential of fruit extracts of Ficus hispida L. and Ficus exasperata Vahl (International Journal of Environmental Sciences, 2024)
Ficus hispida and Ficus exasperata are medicinally important species traditionally used for the treatment of various ailments; however, comparative information on their phytochemical composition and biological activities remains limited. The present study aimed to evaluate the phytochemical constituents, antibacterial activity, and antioxidant potential of fruit extracts of both species. Fruits were extracted using methanol, chloroform, and petroleum ether, followed by qualitative phytochemical screening, antibacterial evaluation against Staphylococcus aureus, Escherichia coli, Pseudomonas aeruginosa, Klebsiella pneumoniae, and Serratia marcescens using the disc diffusion method, and antioxidant assessment by Ferric Reducing Antioxidant Power (FRAP) assay. Phytochemical analysis revealed that methanolic extracts of both species contained the highest number of bioactive constituents, including flavonoids, phenolics, tannins, terpenoids, cardiac glycosides, phytosterols, and saponins, whereas phlobatannins were absent in all extracts. Antibacterial activity increased with extract concentration, with the chloroform extract of F. exasperata exhibiting the strongest activity against P. aeruginosa (16.16 ± 0.48 mm) and S. aureus (15.50 ± 0.62 mm) at 30 mg concentration. In F. hispida, the maximum inhibition zone was observed against S. aureus (14.50 ± 0.62 mm). FRAP analysis demonstrated concentration-dependent antioxidant activity, with methanolic extracts showing the greatest reducing power. The methanolic extract of F. exasperata exhibited the lowest IC₅₀ value (31.63 µg mL⁻¹), followed by F. hispida (33.32 µg mL⁻¹), compared with ascorbic acid (25.50 µg mL⁻¹). The results indicate that both species possess significant antibacterial and antioxidant properties, with F. exasperata showing comparatively superior biological activity, supporting its potential as a natural source of bioactive compounds for pharmaceutical and nutraceutical applications.